Gun Dealer Motivations for Complying with the Law: Lessons from the Australian Experience of Gun Control. (February 2022) - Fay, Suzanna
Gun reform after a major mass shooting in Australia has largely been heralded as a success. However, understanding how compliance is encouraged among the gun owning community with a history of opposing regulation is currently limited in systematic sociological research. Gun dealers in particular appear to be important for understanding levels of compliance and possibilities for promoting compliance, as they are simultaneously involved in the compliance process and subject to its enforcement as members of the gun owning community. This paper positions gun dealers as street-level bureaucrats responsible for implementing gun regulations and uses a Compliance Motivation framework to explore the possible motivations for compliance and their role in promoting compliance within the gun owning community. Findings are based on 28 in-depth interviews with gun dealers across Australia and demonstrate the challenging but important role that gun dealer's play in enacting gun control policy.